My dog's a scaredy-cat : a Halloween tail - Winkler, Henry, 1945- (Winkler, Henry, 1945- Hank Zipzer, 2006)
Teased by the school bully because of his Halloween costume, underachieving Hank, with the help of his friends, exacts revenge by creating the scariest and grossest haunted house ever and inviting the bully to visit.